INCREASING ANTENNA INTERFERENCE SUPPRESSOR EFFICIENCY BY DIVIDING THE BANDWIDTH TO NARROW SUB-BANDS - I. M. Sokolov (Научный вестник МГТУ ГА, 2016)
This article reviews a method of increasing antenna interference suppressor efficiency by dividing the bandwidth of multichannel receiver to narrow sub-bands. Also the principal possibility of the suppression ratio increase on 3-8 dB is proved here. The results of the seminatural experiments made with the use of samples of digitized receiver signal are shown in the article.